The Principle of Fiduciary Duty in Single-Member Limited Liability Company - Simbolon, Yolanda (Perspektif Hukum, 2024)
Limited Liability Company in Indonesia has a conceptual expansion since the Job Creation Law has enacted. There are two types of Limited Liability Company currently, capital partnership limited liability company and single-member limited liability company. One of the most significant changes to the concept of limited liability company is related to its organs. Single-member limited liability company consists of director who also serve as shareholder. The expansion concept raises questions regarding the application of fiduciary duty to single-member limited liability company. This research uses conceptual and statute approach. The conclusion from this research is that in single-member limited liability company, there is only director who also become shareholder, thus there is no supervisory function by the board of commissioner. Secondly, the director in single-member limited liability company still has the obligation to carry out the responsibilities with the principle of fiduciary duty.